Underwater endoscopic mucosal resection: a new endoscopic method for resection of rectal neuroendocrine tumor grade 1 (carcinoid) ≤ 10 mm in diameter - Yamashina, Takeshi; Tumura, Takehiko; Maruo, Takanori; Matsumae, Takayuki; Yoshida, Hiroyuki; Tanke, Gensho; Taki, Mio; Fukuhara, Manabu; Kimura, Yoshito; Sakamoto, Azusa; Henmi, Shinichiro; Sawai, Yugo; Saito, Sumio; Nishijima, Norihiro; Nasu, Akihiro; Komekado, Hideyuki; Asada, Masanori; Kita, Ryuichi; Kimura, Toru; Osaki, Yukio (Endoscopy International Open, 2018)
Background and study aims Rectal neuroendocrine tumors grade 1 (NET G1; carcinoid) ≤ 10 mm in diameter often extend into the submucosa, making their complete histological resection difficult using endoscopic techniques. Endoscopic submucosal resection with a ligation device (ESMR-L) and endoscopic submucosal dissection (ESD) are commonly used to overcome these difficulties. We also previously reported that underwater endoscopic mucosal resection (UEMR) could facilitate resection of rectal NET G1. This study aimed to evaluate the safety and efficacy of UEMR for removing rectal NET G1 ≤ 10 mm in diameter. 6 consecutive patients with rectal NET G1 ≤ 10 mm in diameter underwent UEMR at our hospital. The rate of en bloc resection was 100 %, and the rate of R0 resection was 83 %. The median procedure time was 8 min (range 5 – 12 min). No perforations or delayed bleeding occurred in this study. In conclusion, UEMR allows the safe and reliable resection of rectal NET G1 ≤ 10 mm in diameter with comparable results to ESMR-L or ESD, including high en bloc and R0 resection rates with no increase in significant adverse events. A multicenter trial is required to confirm the validity of the present results.